The Effect of Using Close Reading and GIST Strategies on Students’ Reading Comprehension at Health Vocational High School Pekanbaru - ., TAQIYUDDIN . (State Islamic University of Sultan Syarif Kasim Riau, 2018)
Based on the researcher’s preliminary observation at Health Vocational High School Pekanbaru, it was found that some of the first grade students had problems in reading comprehension, especially in descriptive text. They could not identify the of the text, main idea, supporting details, inference and reference in the text. The main focus of this research was to find out whether there was a significant difference between using Close Reading and GIST strategies on students’ reading comprehension in descriptive text at Health Vocational High School Pekanbaru. It was carried out based on a quasi-experimental design by comparing two strategies of experimental group 1 and experimental group 2 pretest-posttest design. It involved 60 participants that consisted of experimental group 1 and experimental group 2. Four research questions and Four hypotheses were posed in this study in order to find out the significant difference between the use of Close Reading and GIST strategies on the students’ reading comprehension. Pre-test and post-test were administered to collect the data. Then, independent sample t-test and paired sample t-test were used to analyze the collected data. The research findings showed that There is no significant difference on students’ reading comprehension gain score between those students who were taught by close reading and GIST strategies at Health Vocational High School Pekanbaru and also there was a significance difference of post-test mean scores between the experimental class 1 (using Close Reading strategy) and the experimental class 2 (using GIST strategy) on the students’ reading comprehension. Close Reading strategy contributed 79% of their reading comprehension improvement; while GIST contributed 71% of the improvement; In conclusion, both Close Reading and GIST strategies can be applied in teaching reading comprehension at Health Vocational High School Pekanbaru.